FLIPPED CLASSROOM IMPLEMENTATION ON MECHANISM OF NUTRIENT HANDLING TO FACILITATE MULTIPLE PERSPECTIVE APPROACH - Meliala, Andreanyta; Sumiwi, Yustina Andwi Ari; Nuryana, Ch.Tri; Sunarti, Sunarti; Narwidina, Paramita (Universitas Gadjah Mada, 2023)
Background: Due to the content of lectures for nutrient handling often delivered from one scientific discipline, students do not gain a comprehensive understanding. The flipped classroom learning approach helps improve students' overall comprehension by integrating multiple scientific disciplines such as physiology, anatomy, biochemistry, and histology.Aims: The purpose of this study is to assess the efficacy of the flipped classroom learning approach in nutrition management lectures that incorporate physiology, anatomy, biochemistry, and histology.Methods: A basic pre-post test design was employed in this research. The flipped classroom method was used by first asking students to learn the topic via instructional videos, lecture files, and a pre-test (58 questions) on the eLOK UGM platform. The panel discussion was then carried out by lectures from four departments, including physiology, anatomy, biochemistry, and histology, via the Zoom platform (virtual synchronous learning). Finally, students were required to do a post-test with the same content as the pre-test.Results: According to the findings of this study, the average pre-test score of college participants was less than 80, whereas the average post-test score was 84.22, with 73.20% of the participants scoring higher than 80. The integrated panel discussion affected male participants' N-Gain scores. Male participants scored 0.74 (high category) while female participants scored 0.69 (medium category). Conclusions: The flipped classroom method can support approaches from departments of anatomy, physiology, histology, and biochemistry - in a relatively time-efficient but more effective means of improving understanding of nutrient handling.